2005
DOI: 10.1016/j.febslet.2005.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of inclusion body formation studied in intact cells by FT‐IR spectroscopy

Abstract: The aggregation of a recombinant lipase as inclusion bodies (IBs) was studied directly within intact Escherichia coli cells by FT-IR microspectroscopy. Through this approach, it was possible to monitor in real time the different kinetics of IB formation at 37 and 27°C, in excellent agreement with the results of the SDS-PAGE analysis. Furthermore, insights on the residual native-like structure of the expressed protein within IB -both isolated and inside cells -were obtained by the secondary structure analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 15 publications
2
72
1
Order By: Relevance
“…The conformational background sustaining the IB molecular structure lies on an extended, intermolecular ␤-sheet architecture (6) that coexists with various amounts of a population of native-like, correctly folded polypeptides (1)(2)(3)26). Such a ␤-sheet pattern is progressively lost at the expense of native-like structure when the temperature at which IBs are formed decreases (19,28), indicating the existence of several categories of protein aggregates in regard to their molecular organization and even global morphology (13).…”
mentioning
confidence: 99%
“…The conformational background sustaining the IB molecular structure lies on an extended, intermolecular ␤-sheet architecture (6) that coexists with various amounts of a population of native-like, correctly folded polypeptides (1)(2)(3)26). Such a ␤-sheet pattern is progressively lost at the expense of native-like structure when the temperature at which IBs are formed decreases (19,28), indicating the existence of several categories of protein aggregates in regard to their molecular organization and even global morphology (13).…”
mentioning
confidence: 99%
“…This work highlights the potential of FT-IR spectroscopy not only to study protein aggregation in IBs [6][7][8], but also to monitor the membrane response induced by the heterologous production.…”
Section: Resultsmentioning
confidence: 92%
“…The method enables us to monitor the kinetics of aggregate formation within intact cells in a rapid and non invasive way and to obtain structural information on proteins within IBs. We will report results on four recombinant proteins: human growth hormone (h-GH), human interferon-alpha-2b (IFN-alpha-2b) [4,7], Pseudomonas fragi lipase [3], and green fluorescent protein -glutathione S-transferase fusion protein (GFP-GST) [8].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been suggested that the presence of native-like structures within IBs [1][2][3][4] improves the efficiency of refolding protocols that employ mild solubilization methods [5]. This property could also explain the residual enzymatic activity of recombinant proteins in IBs, with possible applications in biocatalysis [6].…”
Section: Introductionmentioning
confidence: 99%